2018
DOI: 10.1002/lno.10788
|View full text |Cite
|
Sign up to set email alerts
|

Methylotrophic methanogenesis fuels cryptic methane cycling in marine surface sediment

Abstract: Methylotrophic methanogenesis is often proposed to be responsible for methane production in sulfate‐rich environments, yet the magnitude of this process remains elusive. In this study, we incubated sediment from Aarhus Bay (Denmark) with 13C labeled CH4 to measure total methane turnover by isotope dilution, and with 14C‐radiotracers to measure specifically the gross hydrogenotrophic and acetoclastic methane production. Highest CH4 production rates (> 200 pmol cm−3 d−1) were found in the top 0–2 cm. Most of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…Although hydrogenotrophic methanogenesis was also detected at ROV2 and ROV3, the higher turnover of methylated compounds as well as the dominance of methylotrophic methanogens ( see below) suggested the methylotrophic pathway could be important for the concurrent methanogenesis with SR in the sulfate‐reducing sediments. Those results were in aggreement with previous studies, which experiemntally demonstrated that methane production in sulfate‐rich sediment could be driven by the fermentation of methylated compounds (Maltby et al ; Xiao et al ; Zhuang et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Although hydrogenotrophic methanogenesis was also detected at ROV2 and ROV3, the higher turnover of methylated compounds as well as the dominance of methylotrophic methanogens ( see below) suggested the methylotrophic pathway could be important for the concurrent methanogenesis with SR in the sulfate‐reducing sediments. Those results were in aggreement with previous studies, which experiemntally demonstrated that methane production in sulfate‐rich sediment could be driven by the fermentation of methylated compounds (Maltby et al ; Xiao et al ; Zhuang et al ).…”
Section: Discussionsupporting
confidence: 91%
“…As an alternative to a benthic source, methane could be produced in the water column as previously suggested (Sansone et al ) and supported by the detection of transcriptionally active methanogenic archaea at anoxic depths in the OMZ (Padilla et al ). Concomitant production and oxidation of methane has been observed in marine surface sediment, where the production is based on C 1 compounds that are not utilized by the otherwise dominating sulfate reducing bacteria (Xiao et al , ). Although methylotrophic methanogens in OMZ waters should face strong competition from nitrate/nitrite‐respiring methylotrophs (Beck et al ), they could potentially be active in nitrate and nitrite‐depleted microniches, e.g., inside organic‐rich aggregates (Bianchi et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar trend was observed without molybdate addition and in N 2 amended controls ( Supplementary Figures S3-S5). The stimulation of ANMEs in the N 2 controls might have been due to methane supply via co-occurring methanogenesis in these incubations (Supplementary Figure S6) recently termed "cryptic methane cycling" and detected in the SMT of Aarhus Bay and other marine sediments Maltby et al, 2018;Xiao et al, 2018).…”
Section: Microbial Key Players Involved In Fe-aommentioning
confidence: 96%